2016
DOI: 10.1007/s10461-016-1387-9
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Three Novel HIV Prevention Methods Among Young Male and Transgender Female Sex Workers in Puerto Rico

Abstract: Male and transgender female (TGF) sex workers need HIV-prevention methods they can control and incorporate easily in their work. We explored acceptability of the use of the HIV self test with clients, oral pre-exposure prophylaxis (PrEP), and rectal microbicide gel among 12 male and TGF sex workers in Puerto Rico. At baseline, we measured likelihood of use of each method. Five sex workers also completed a 12-week study of rectal microbicide placebo gel use prior to receptive anal intercourse with clients and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 34 publications
(13 reference statements)
3
19
0
Order By: Relevance
“…Our study showed a preference for blood-based kits, which is similar to findings from studies in the USA, Malawi and Zimbabwe [23,24]. Also our findings of preferences for a low or no cost to the user for HIVST kits, resonate with studies conducted in a wide range of settings (high to low income) and within general and key populations [23,25,26]. These characteristics provide an inclusive HIVST program that increases access for testing particularly for those belonging to a low socioeconomic group [27,28].…”
Section: Discussionsupporting
confidence: 88%
“…Our study showed a preference for blood-based kits, which is similar to findings from studies in the USA, Malawi and Zimbabwe [23,24]. Also our findings of preferences for a low or no cost to the user for HIVST kits, resonate with studies conducted in a wide range of settings (high to low income) and within general and key populations [23,25,26]. These characteristics provide an inclusive HIVST program that increases access for testing particularly for those belonging to a low socioeconomic group [27,28].…”
Section: Discussionsupporting
confidence: 88%
“…While PrEP willingness in TGW is high , several challenges limit PrEP use and efficacy. Barriers to PrEP uptake in TGW include concerns about side effects and the effect of PrEP drugs on gender‐affirming hormone treatment (GAHT), limited transgender‐inclusive PrEP promotion, and medical mistrust . The iPrEx trial of oral daily tenofovir disoproxil fumarate (TDF) 300 mg/emtricitabine (FTC) 200 mg (Truvada TM Gilead Sciences, Inc. Foster City, CA) showed efficacy in men who have sex with men (MSM) and TGW, collectively .…”
Section: Introductionmentioning
confidence: 99%
“…Only three studies have explored perceptions of HIVST among sex workers—each from Puerto Rico, China, and Kenya [ 21 23 ]. In Puerto Rico, male and transgender female sex workers voiced concerns about confidentiality and triggering violence with clients [ 21 ]. In China, sex workers reported high acceptability of oral HIVST kits, but doubted the accuracy of the results [ 22 ].…”
Section: Introductionmentioning
confidence: 99%